2015
DOI: 10.1371/journal.pmed.1001925
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery in the United Kingdom: A Cohort Study of Weight Loss and Clinical Outcomes in Routine Clinical Care

Abstract: BackgroundBariatric surgery is becoming a more widespread treatment for obesity. Comprehensive evidence of the long-term effects of contemporary surgery on a broad range of clinical outcomes in large populations treated in routine clinical practice is lacking. The objective of this study was to measure the association between bariatric surgery, weight, body mass index, and obesity-related co-morbidities.Methods and FindingsThis was an observational retrospective cohort study using data from the United Kingdom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 36 publications
7
139
2
2
Order By: Relevance
“…Gastric bypass and sleeve gastrectomy are associated with greater initial weight reduction rate than gastric banding [96]. Trends in body weight post-surgically show that patients undergoing RYGB exhibit the greatest weight loss, patients undergoing SG experience less weight loss and patients undergoing AGB have the least weight loss [97].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Gastric bypass and sleeve gastrectomy are associated with greater initial weight reduction rate than gastric banding [96]. Trends in body weight post-surgically show that patients undergoing RYGB exhibit the greatest weight loss, patients undergoing SG experience less weight loss and patients undergoing AGB have the least weight loss [97].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Even those persistently obese women, benefit from a 50% lowering of endometrial cancer risk following surgery, suggesting that metabolic changes, such as improvements in insulin sensitivity, are also important in this context (12). Additional health benefits associated with bariatric surgery include a reduction in the incidence of other obesity-related cancers, including postmenopausal breast and colorectal cancer, as well as resolution of diabetes, hypertension, angina, and obstructive sleep apnea (13). These benefits need to be incorporated into cost-effectiveness studies when determining the value of weight loss surgery in cancer prevention.…”
Section: Bmimentioning
confidence: 99%
“…Sustained weight loss, reduced mortality, and improved hyperglycemia and hypertension are all advantages of BS [8][9][10][20][21][22]. As with any procedure there are risks associated with BS.…”
Section: Discussionmentioning
confidence: 99%
“…BS results in sustained weight loss and improves hyperinsulinemia, hyperglycemia, dyslipidemia, and hypertension even after 6 months [8][9][10]21]. Douglas et al suggested that BS is associated with protective hazard ratios for type-2 diabetes mellitus, hypertension, angina, and myocardial infarction [22]. Furthermore, a 40,000 patient observational study suggested that BS was associated with a 46% reduction in heart failure compared to lifestyle interventions [23].…”
Section: Transplantation After Donor Bariatric Surgerymentioning
confidence: 99%